2012
DOI: 10.2174/138161212803251943
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Aspirin in Ischemic Heart Disease: Past, Present and Future

Abstract: Aspirin is an antiplatelet drug, inhibiting the cyclooxygenase activity of platelet prostaglandin H synthase-1 and almost complete suppressing platelet capacity to generate the prothrombotic and proatherogenic thromboxane A2. Antiplatelet therapy with aspirin reduces the risk of serious vascular events by about a quarter in patients who are at high risk because they already have occlusive vascular disease. However, the inhibition of thromboxane-dependent platelet function by aspirin is effective for the preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Aspirin decreases platelet aggregation, inactivating the cyclooxygenase (COX) activity of prostaglandin (PGH)-synthase-1 and PGH synthase-2 (also referred to as COX-1 and COX-2) (De Caterina & Renda, 2012). These enzymes catalyze the change of arachidonate to prostaglandin H 2 (PGH 2 ), which is the precursor of TXA 2 and PGI 2 (Del Gaudio et al, 2013).…”
Section: Determination Of Blood Clotting Timesmentioning
confidence: 99%
“…Aspirin decreases platelet aggregation, inactivating the cyclooxygenase (COX) activity of prostaglandin (PGH)-synthase-1 and PGH synthase-2 (also referred to as COX-1 and COX-2) (De Caterina & Renda, 2012). These enzymes catalyze the change of arachidonate to prostaglandin H 2 (PGH 2 ), which is the precursor of TXA 2 and PGI 2 (Del Gaudio et al, 2013).…”
Section: Determination Of Blood Clotting Timesmentioning
confidence: 99%
“…The beneficial efficacy of aspirin for primary prevention of vascular thrombosis is counterbalanced by hazards of excess bleeding, which has resulted in critically selecting subjects at increased risk of thrombosis for prevention after considerable evaluation for the existing risk of bleeding [40,41]. Conversely, the benefits of aspirin for secondary prevention clearly outweigh the risks of bleeding, thus aspirin continues to be fundamental of antithrombotic therapy as secondary prevention in coronary, cerebral as well as peripheral vascular thrombotic events.…”
Section: Site Of Action Of Antiplatelet Therapiesmentioning
confidence: 99%
“…We all know that this medicine can be used to treat colds, fever, headaches, toothache, joint pain, and rheumatism. It also can inhibit platelet aggregation, prevent and treat ischemic heart disease, cardiopulmonary infarction, cerebral thrombosis and other diseases (De and Renda, 2012). In addition, it has shown that acetylsalicylic acid has anti-cancer effect (Rothwell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%